2018
DOI: 10.1111/cdev.13024
|View full text |Cite
|
Sign up to set email alerts
|

Children's Perceptions of Economic Groups in a Context of Limited Access to Opportunities

Abstract: Children (N = 267, ages 8-14 years, M = 11.61 years, middle to upper-middle income) made predictions regarding groups of same-aged peers from high-wealth and low-wealth backgrounds. The context involved granting access to a special opportunity. From middle childhood to early adolescence children increasingly expected both high- and low-wealth groups to want access to opportunities for their own group. However, children viewed high-wealth groups as motivated in part by selfishness and low-wealth groups as conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 73 publications
(126 reference statements)
3
45
0
2
Order By: Relevance
“…The idea that children and adolescents may perceive wealth to be an indicator of group exclusivity fits well with previous research relating wealth to status more generally (e.g., Olson, Shutts, Kinzler, & Weisman, 2012), and with recent studies indicating that children sometimes hold negative perceptions of high-wealth peers (Elenbaas & Killen, 2018). No distinctions were made, however, between highwealth European American groups and high-wealth African American groups in this context.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The idea that children and adolescents may perceive wealth to be an indicator of group exclusivity fits well with previous research relating wealth to status more generally (e.g., Olson, Shutts, Kinzler, & Weisman, 2012), and with recent studies indicating that children sometimes hold negative perceptions of high-wealth peers (Elenbaas & Killen, 2018). No distinctions were made, however, between highwealth European American groups and high-wealth African American groups in this context.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding children's predictions of group exclusivity, we predicted that: (H1) with age, children would predict that high‐wealth groups, regardless of their race, would be more exclusive than lower wealth groups; (H2) with age, children would increasingly reference negative stereotypes about high‐wealth groups in justifying their perceptions, as recent studies have shown that the negative stereotypes associated with high‐wealth individuals may be especially salient in peer contexts (Elenbaas & Killen, ).…”
Section: Children's Social Group Understanding About Wealthmentioning
confidence: 99%
See 2 more Smart Citations
“…Wealth is a continuum, yet children and adults tend to separate the spectrum into distinct groups and use labels like "rich," "middle class," and "poor" in daily life (Elenbaas & Killen, 2018;Kraus, Park, & Tan, 2017;Mistry, Brown, White, Chow, & Gillen-O'Neel, 2015;Stephens, Markus, & Phillips, 2014). For instance, young children identify individuals as rich or poor based on cues from their clothing and possessions (Chafel & Neitzel, 2005;Rauscher, Friedline, & Banerjee, 2017).…”
mentioning
confidence: 99%